-9(2b+3)+(19b-5)=0

Simple and best practice solution for -9(2b+3)+(19b-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(2b+3)+(19b-5)=0 equation:


Simplifying
-9(2b + 3) + (19b + -5) = 0

Reorder the terms:
-9(3 + 2b) + (19b + -5) = 0
(3 * -9 + 2b * -9) + (19b + -5) = 0
(-27 + -18b) + (19b + -5) = 0

Reorder the terms:
-27 + -18b + (-5 + 19b) = 0

Remove parenthesis around (-5 + 19b)
-27 + -18b + -5 + 19b = 0

Reorder the terms:
-27 + -5 + -18b + 19b = 0

Combine like terms: -27 + -5 = -32
-32 + -18b + 19b = 0

Combine like terms: -18b + 19b = 1b
-32 + 1b = 0

Solving
-32 + 1b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '32' to each side of the equation.
-32 + 32 + 1b = 0 + 32

Combine like terms: -32 + 32 = 0
0 + 1b = 0 + 32
1b = 0 + 32

Combine like terms: 0 + 32 = 32
1b = 32

Divide each side by '1'.
b = 32

Simplifying
b = 32

See similar equations:

| 8x+2=5x+17 | | 1.3(8-x)+3.7x=-5.2 | | -2(x+3)+3x=11 | | 6z^2+43z+7*7z^2+4z-6= | | 27=2m+7-m+3-2m-1 | | 6b-0.4=7b | | -18y+9y= | | 10-8x=90-36x | | (5v+6)(4-v)=0 | | .25x+.1x=9.8 | | 3[(1)]=x | | 2p+22p^2-p= | | 3[(1)]= | | x^2+31x+5=0 | | Y=-5x+18 | | 24p-28q= | | .25y-10=.1y | | 17+5/15=-4 | | .4x-4=2.8+.2x | | (s/3)+11=16 | | 7+9+x=40 | | 1.12+1.15x=8.62 | | -4t^2+30t-12=0 | | 6-7m-20m^2=0 | | -16+51=-5(x+5) | | 1.12+1.12x=8.62 | | 5=4x-10 | | 8x^2+kx+k=0 | | (4z+1)(8-z)=0 | | 17x-5=11x-35 | | 22+4b=-2(1-6b) | | -0.7x+9.24=-0.5x+8.24 |

Equations solver categories